Assessment of right and left ventricular perfusion in patients with right bundle branch block - TOKAY TARHAN, SENA (ELSEVIER SCIENCE INC, 2006)
Background. Patients with conduction abnormalities may have abnormal images on perfusion scintigraphy without evidence of coronary artery disease (CAD). Based on the presence of left ventricular perfusion abnormalities in left bundle branch block and taking advantage of the Tc-99m sestamibi for the assessment of myocardial perfusion of both ventricles, we aimed to evaluate right (RV) and left (LV) myocardial perfusion in patients with right bundle branch block (RBBB). Methods. This study included 21 patients with RBBB and 21 control subjects without conduction abnormality. None had previous myocardial infarction, known CAD, left ventricular hypertrophy, LVEF <55%, congenital, pulmonary or valvular heart disease. Rest and stress SPECT images were obtained using 1-d Tc-99m sestamibi SPECT protocol. Regional perfusion of LV and RV myocardium was semiquantitatively evaluated. Also, RV/LV uptake ratio was calculated in two different ways. Results. In patients with RBBB, the normality ratios of RV and LV myocardial perfusion were very high (both 90.5%) and not different from those of patients with normal intraventricular conduction. In the comparison of RV/LV uptake ratios, no significant difference was found between the RBBB and control groups. Conclusions. LV perfusion, RV perfusion or R-to-L perfusion ratio were not significantly influenced by the conduction abnormality in this selected patient population with RBBB. Tc-99m sestamibi myocardial scintigraphy could help in the exclusion of myocardial ischemia in patients with RBBB. (C) 2006 IMSS. Published by Elsevier Inc.
Keywords: conduction abnormality; myocardial perfusion; right bundle branch block; right ventricle; EMISSION COMPUTED-TOMOGRAPHY; CORONARY-ARTERY-DISEASE; INFERIOR MYOCARDIAL-INFARCTION; DILATED CARDIOMYOPATHY; GATED SPECT; EXERCISE; DEFECTS; FALSE; ABNORMALITIES; DYSFUNCTION